T. S. Eliot and Transpacific Modernism. (27th September 2015) - Patterson, Anita
Abstract : Japonisme is a term often used to describe the shaping effects of Japanese culture and aesthetics on European art, but by the 1880s a similar trend emerged in the US, influencing popular culture as well as fine arts and poetry. This essay examines how Japonisme figured T. S. Eliot's development as a poet, focusing on Boston as a world city that was rapidly becoming global. It shows how Kakuzo Okakura, an art historian and curator of Asian art at the Boston Museum of Fine Arts during the time when Eliot was a Harvard undergraduate, and Masaharu Anesaki, a pioneer in the study of comparative religion who lectured on Mahayana Buddhism there when Eliot was a graduate student, inspired transpacific intercultural dialogue that would last the poet a lifetime. Eliot's formative encounter with Okakura and Anesaki raised his awareness of his family history in a region with longstanding ties to Asia; it nurtured his ambivalent engagement with such Boston-area writers as Emerson, whose prior interest in Confucianism laid a foundation for Eliot's modernism; and the encounter taught Eliot valuable lessons about moral action and impersonality, culminating in poems such as Four Quartets .